Do Firms Use Tax Reserves to Meet Analysts’ Forecasts? Evidence from the Pre‐ and Post‐FIN 48 Periods - Gupta, Sanjay; Laux, Rick C.; Lynch, Daniel P. (Contemporary Accounting Research, 2016)
Abstract We examine whether firms decrease tax reserves to meet analysts’ quarterly earnings forecasts in the period prior to FIN 48, and whether that behavior changed following FIN 48. We use analysts’ forecasts of pretax and after‐tax income to impute premanaged earnings, or earnings before any tax manipulation. Pre‐ FIN 48, we observe that firms reduce their tax reserves (i.e., increase income) when premanaged earnings are below analysts’ forecasts. Specifically, 78 percent of firm‐quarters that would have missed the analyst forecast if not for the tax reserve decrease, meet that target when the decrease is included. Furthermore, we find a significant positive association between the decrease in tax reserves and the deviation of premanaged earnings from analysts’ forecasts. In contrast, post‐ FIN 48, we find no evidence that firms use changes in tax reserves to manage earnings to meet analysts’ forecasts. Thus, our results suggest that FIN 48 has, at least initially, curtailed firms’ use of tax reserves to manage earnings.